Healthcare employees' perception on information privacy concerns - Rahim F.A.; Ismail Z.; Samy G.N. (IEEE Computer Society, 2023)
Data privacy; Information systems; Medical computing; Metadata; Societies and institutions; Electronic medical record; Healthcare organisations; Information privacy concerns; Patient information; Privacy awareness; Privacy breaches; Quantitative data; Structural equation modeling; Health care